PENGUATAN PRESIDENSIALISME DALAM KEHIDUPAN SOSIAL DI INDONESIA - Mamang, Damrah (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
Social justice is a society or the nature of a society that is just and prosperous, happy for everyone, not insulting, because we must end this extreme poverty as quickly as possible in order to create social justice for all Indonesian people.The functional flow, which considers the facts of state development and people's problems to be increasingly comprehensive, makes it very difficult to strictly separate the functions of the organs administering state power without any coordination between these organs. This flow of argumentation is based on the assumption of making the task of administering state power effective and efficient, so that the target of achieving people's welfare can be realized quickly. Examining from a historical perspective the theory and practice of constitutional law can be traced from juridical documents, especially those originating from the text of the 1945 Constitution and explanations before the changes to the 1945 Constitution itself. In the explanation of point V, it is formulated that the President is not responsible to the DPR. Beside the President is the DPR. The president must obtain approval from the DPR to form a law (Gezetzgebung) and to determine the state revenue and expenditure budget (Staatsbegrooting). Therefore, the President must cooperate with the Council, but the President is not responsible to the Council, meaning that the president's position does not depend on the Council.